Evaluating risks in software negotiations through fuzzy cognitive maps - Papatheocharous, Efi; Andreou, Andreas S.; Rodrigues, Sergio Assis; De Souza, Jano Moreira (My University, 2009)
Risks are inevitably and permanently present in software negotiations and they can directly influence the success or failure of negotiations. Risks should be avoided when they represent a threat and encouraged when they denote an opportunity. This work examines the influence of some negotiation elements in the area of risk and cost estimation, which are both factors that directly influence software development negotiation. In this work, risk quantification is proposed to translate its impact to measurable values that may be taken into consideration during negotiations. The model proposed involves an assessment tool based on basic negotiation elements - namely relationship, interests, cost and time - quantifying the influences among each other, and makes use of Fuzzy Cognitive Maps (FCMs) for developing the associations around basic risk elements on one hand and attaining an innovative risk quantification model for improved software negotiations on the other. Indicative scenarios are presented to demonstrate the efficacy of the proposed approach.
Keywords: Cost estimation; Decision making process; Fuzzy cognitive map; Negotiation; Risk management